2013
DOI: 10.1007/s11033-013-2847-1
|View full text |Cite
|
Sign up to set email alerts
|

Purvalanol A is a strong apoptotic inducer via activating polyamine catabolic pathway in MCF-7 estrogen receptor positive breast cancer cells

Abstract: Purvalanol A is a specific CDK inhibitor which triggers apoptosis by causing cell cycle arrest in cancer cells. Although it has strong apoptotic potential, the mechanistic action of Purvalanol A on significant cell signaling targets has not been clarified yet. Polyamines are crucial metabolic regulators affected by CDK inhibition because of their role in cell cycle progress as well. In addition, malignant cells possess impaired polyamine homeostasis with high level of intracellular polyamines. Especially induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In our previous study, we determined that 30 µM purvalanol induced apoptotic cell death by modulating the expression of the Bcl-2 family members via activating polyamine catabolic metabolism in HCT 116 colon cancer cells (7). Another previous study from our laboratory showed that 25 µM purvalanol induced apoptosis via activation of caspases, which led to dysfunction of MMP in MCF-7 breast cancer cells (6). A lower dose of purvalanol (15 µM) used in this study also inhibited cell proliferation via cell cycle arrest and induced cell death through MMP loss figure 5.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our previous study, we determined that 30 µM purvalanol induced apoptotic cell death by modulating the expression of the Bcl-2 family members via activating polyamine catabolic metabolism in HCT 116 colon cancer cells (7). Another previous study from our laboratory showed that 25 µM purvalanol induced apoptosis via activation of caspases, which led to dysfunction of MMP in MCF-7 breast cancer cells (6). A lower dose of purvalanol (15 µM) used in this study also inhibited cell proliferation via cell cycle arrest and induced cell death through MMP loss figure 5.…”
Section: Discussionmentioning
confidence: 97%
“…Intracellular polyamine levels are under the control of several catabolic enzymes, such as spermidine/spermine-N-acetyl transferase (SSAT). Although purvalanol-induced cell cycle arrest and apoptotic cell death were demonstrated in prostate (5), breast (6) and colon cancer cells (7), the exact molecular mechanism of purvanol-induced apoptosis has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Roscovitine is a new-generation CDK inhibitor that induces apoptosis via blocking the cell cycle at G 1 /S and G 2 /M checkpoints through activation of caspases and cytochrome-c release (Henfling et al, 2004). In vitro studies showed that roscovitine is a promising therapeutic agent in prostate (Arisan et al, 2014), leukemia (Hahntow et al, 2004), and breast (Obakan et al, 2014) cancer. Moreover, roscovitine has been shown to induce cell cycle arrest and apoptosis in ER-MDA-MB-231 breast cancer cells (Mgbonyebi et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in our recent study with endoxifen and by other studies, SMO induction is a remarkable chemotherapeutic target [ 36 , 71 , 72 , 73 ]. Purvalanol, a specific CDK inhibitor with apoptosis inducing activity in breast cancer cells, also induced SSAT, APAO and SMO in MCF-7 and MDA-MB-231 breast cancer cells [ 74 ]. Cervelli et al [ 43 ] analyzed SMO mRNA and enzyme activity in breast cancer tissues and non-tumor samples.…”
Section: Polyamine Analogues and Breast Cancer Therapeuticsmentioning
confidence: 99%